Selective CO2 Adsorption By Methyl‐Functionalized Metal‐Organic Framework. Issue 26 (12th September 2017) - Ma, Deyun; Li, Zhi; Jiang, Fei; Ma, Yanhua; Lin, Wanchun; Wen, Meiling; Liu, Bei; Xu, Jun
Abstract: A hydrophobic porous MOF functionalized by methyl groups with a chemical formula [Cd2 (oba)2 (dmbpy)(H2 O)]⋅2(EtOH)⋅4(H2 O)n (1 ) (oba=4, 4′‐oxydibenzoate, dmbpy=3, 3′‐dimethyl‐4, 4′‐bipyridine, EtOH=ethanol) was synthesized and structurally characterized.1 exhibits a 3D framework with a 1D channel parallel to the c axis. TGA, PXRD, and water vapor sorption results show high thermal and water stability for the framework. More importantly, 1 shows a very high adsorption selectivity to CO2 as compared to other small gas molecules (e. g. CH4, N2, O2, CO and H2 ) at 298 K based on the results of simulations and experiments. Abstract : A hydrophobic and methyl‐functionalized Cd‐based 3D MOF is designed that shows a very high adsorption selectivity to CO2 as compared to other small gas molecules (e. g. CH4, N2, O2, CO and H2 ) at 298 K based on the results of simulations and experiments.